Prevalence of G6PD deficiency in selected populations from two previously high malaria endemic areas of Sri Lanka. - Sharmini Gunawardena; G M G Kapilananda; Dilhani Samarakoon; Sashika Maddevithana; Sulochana Wijesundera; Lallindra V Goonaratne; Nadira D Karunaweera (PLoS ONE)
Glucose-6-Phosphate Dehydrogenase (G6PD) enzyme deficiency is known to offer protection against malaria and an increased selection of mutant genes in malaria endemic regions is expected. However, anti-malarial drugs such as primaquine can cause haemolytic anaemia in persons with G6PD deficiency. We studied the extent of G6PD deficiency in selected persons attending Teaching Hospitals of Anuradhapura and Kurunegala, two previously high malaria endemic districts in Sri Lanka. A total of 2059 filter-paper blood spots collected between November 2013 and June 2014 were analysed for phenotypic G6PD deficiency using the modified WST-8/1-methoxy PMS method. Each assay was conducted with a set of controls and the colour development assessed visually as well as with a microplate reader at OD450-630nm. Overall, 142/1018 (13.95%) and 83/1041 (7.97%) were G6PD deficient in Anuradhapura and Kurunegala districts respectively. The G6PD prevalence was significantly greater in Anuradhapura when compared to Kurunegala (P<0.0001). Surprisingly, females were equally affected as males in each district: 35/313 (11.18%) males and 107/705 (15.18%) females were affected in Anuradhapura (P = 0.089); 25/313 (7.99%) males and 58/728 (7.97%) females were affected in Kurunegala (P = 0.991). Prevalence was greater among females in Anuradhapura than in Kurunegala (P<0.05), while no such difference was observed between the males (P>0.05). Severe deficiency (<10% normal) was seen among 28/1018 (2.75%) in Anuradhapura (7 males; 21 females) and 17/1041 (1.63%) in Kurunegala (7 males; 10 females). Enzyme activity between 10-30% was observed among 114/1018 (11.20%; 28 males; 86 females) in Anuradhapura while it was 66/1041 (6.34%; 18 males; 48 females) in Kurunegala. Screening and educational programmes for G6PD deficiency are warranted in these high risk areas irrespective of gender for the prevention of disease states related to this condition.